Prediction of Post-Discharge Bleeding in Elderly Patients with Acute Coronary Syndromes: Insights from the BleeMACS Registry - Garay, Alberto; Ariza-Solé, Albert; Formiga, Francesc; Raposeiras-Roubín, Sergio; Abu-Assi, Emad; Sánchez-Salado, José C.; Lorente, Victòria; Alegre, Oriol; Henriques, Jose Paulo Simao; D'Ascenzo, Fabrizio; Saucedo, Jorge; González-Juanatey, José Ramón; Wilton, Stephen B.; Kikkert, Wouter J.; Nuñez-Gil, Iván; Song, Xiantao; Alexopoulos, Dimitrios; Liebetrau, Christoph; Kawaji, Tetsuma; Moretti, Claudio; Huczek, Zenon; Nie, Shao-Ping; Fujii, Toshiharu; Correia, Luis; Kawashiri, Masa-aki; García-Acuña, José María; Southern, Danielle; Alfonso, Emilio; Terol, Belén; Zhang, Dongfeng; Chen, Yalei; Xanthopoulou, Ioanna; Osman, Neriman; Möllmann, Helge; Shiomi, Hiroki; Giordana, Francesca; Gaita, Fiorenzo; Kowara, Michal; Filipiak, Krzysztof; Wang, Xiao; Yan, Yan; Fan, Jing-Yao; Ikari, Yuji; Nakahashi, Takuya; Sakata, Kenji; Yamagishi, Masakazu; Kalpak, Oliver; Kedev, Sasko; Cequier, Angel (Thrombosis and Haemostasis, 2018)
Background A poor ability of recommended risk scores for predicting in-hospital bleeding has been reported in elderly patients with acute coronary syndromes (ACS). No study assessed the prediction of post-discharge bleeding in the elderly. The new BleeMACS score (Bleeding complications in a Multicenter registry of patients discharged with diagnosis of Acute Coronary Syndrome), was designed to predict post-discharge bleeding in ACS patients. We aimed to assess the predictive ability of the BleeMACS score in elderly patients.Methods We assessed the incidence and characteristics of severe bleeding after discharge in ACS patients aged ≥ 75 years. Bleeding was defined as any intracranial bleeding or bleeding leading to hospitalization and/or red blood transfusion, occurring within the first year after discharge. We assessed the predictive ability of the BleeMACS score according to age by Fine–Gray proportional hazards regression analysis, calculating receiver-operating characteristic (ROC) curves and the area under the ROC curves (AUC).Results The BleeMACS registry included 15,401 patients of whom 3,376/15,401 (21.9%) were aged ≥ 75 years. Elderly patients were more commonly treated with clopidogrel and less often treated with ticagrelor or prasugrel. Of 3,376 elderly patients, 190 (5.6%) experienced post-discharge bleeding. The incidence of bleeding was moderately higher in elderly patients (hazard ratio [HR], 2.31, 95% confidence interval [CI], 1.92–2.77). The predictive ability of the BleeMACS score was moderately lower in elderly patients (AUC, 0.652 vs. 0.691, p = 0.001).Conclusion Elderly patients with ACS had a significantly higher incidence of post-discharge bleeding. Despite a lower predictive ability in older patients, the BleeMACS score exhibited an acceptable performance in these patients.
Keywords: acute coronary syndromes; elderly; bleeding; risk prediction